Recent advances in biosynthesis mechanisms and yield enhancement strategies of erythritol - Wenli Yang; Xiangying Zhao; Mo Han; Yuchen Li; Yanjun Tian; Zhangbo Rong; Jiaxiang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Genetic Causal Association Between 15 Micronutrients and 12 Obstetric-Related Diseases: A Mendelian Randomization Study - Lele Pan; Jing Zhang; Mingwei Chen; Li Yuan; Rong Chen; Lina Zhao (Biological Trace Element Research, 2024)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Predictive models of air temperatures inside a naturally ventilated vehicle transporting weaner pigs - Guoxing Chen; Guoqiang Zhang; Li Rong (Computers and Electronics in Agriculture, 2024)

Path planning of greenhouse electric crawler tractor based on the improved A* and DWA algorithms - Huiping Guo; Yi Li; Hao Wang; Chensi Wang; Jiao Zhang; Tingwei Wang; Linrui Rong; Haoyu Wang; Zihao Wang; Yaobin Huo; Shaomeng Guo; Fuzeng Yang (Computers and Electronics in Agriculture, 2024)

Lipid biomarkers indicate the dynamics of particulate organic carbon and its carbon sequestration effects during the degradation of Ulva prolifera - Miaomiao Zhao; Hongmei Li; Rong Bi; Hailong Zhang; Shengrong Huang; Li Li; Yang Ding; Yongyu Zhang; Meixun Zhao (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Scaled experimental study of a ventilation system featuring partition jet and pit exhaust - Qizhi Yang; Xi Bai; Guoqiang Zhang; Li Rong; Yao Tao; Jiyuan Tu; Jinyong Wang; Zhiru Hu; Jie Chai; Yong Wang (Biosystems Engineering, 2024)

Verifying the reliability of CFD domain decomposition technique on modelling the airflow field inside a naturally ventilated cattle barn - Guoxing Chen; Guoqiang Zhang; Li Rong (Biosystems Engineering, 2024)

Off-site production of plasma-activated water for efficient disinfection: The crucial role of high valence NOx and new chemical pathways - Zifeng Wang; Xiangyu Wang; Shenghang Xu; Renwu Zhou; Mingyan Zhang; Wanchun Li; Zizhu Zhang; Luge Wang; Jinkun Chen; Jishen Zhang; Li Guo; Dandan Pei; et al. (Water Research, 2024)

Mechanism of antimony oxidation and adsorption using immobilized Klebsiella aerogenes HC10 in soil - Qun Rong; Dingtian Lu; Kai Zhong; Shu Yang; Zhongyi Li; Chaolan Zhang (Science of The Total Environment, 2024)

Cascading impacts of nitrogen deposition on soil microbiome and herbivore communities in desert steppes - Jingxi Liu; Mengmeng Zhu; Xiangfeng Shi; Cang Hui; Yurong Sun; Rong Zhang; Decai Jin; Zhihong Li; Honghao Chen; Zihua Zhao (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Invisible hazards: Exploring neonicotinoid contamination and its environmental risks in urban parks across China - Yongfeng Deng; Ruqin Shen; Xue Zhang; Yang Li; Xingguo Chen; Rong-Rong He; Hao Tian; Shuqin Tang; Xiang Luo; Jing Li; Wan-Yang Sun; Hongli Tan (Science of The Total Environment, 2024)

Effects of changing spatial scale on debris-flow hazard assessment: A case study in the Dadu River basin, China - Lili Zhang; Jianqiang Zhang; Zaiyang Ming; Haoyu Li; Rong Chen; Yang Jia (Science of The Total Environment, 2024)

Nitrate Over Ammonium: Limited inorganic N niche partitioning between wheat and weeds regardless of fertilization treatment - Peilin Han; Yizhong Rong; Weiqiang Liu; Jie Liu; Li Zhang (Rhizosphere, 2024)

Physio-mechanical properties of loess-paleosol sequences over the past 400 ka and their paleoclimate controlling factors on the central Loess Plateau - Xiaoning Wang; Dapeng Yue; Jingbo Zhao; Lixing Zhang; Rong Liu; Jianing Li; Yueshan Liu (Quaternary Science Reviews, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Recycle of residual ammonium from weathered crust elution-deposited rare earth tailings via an efficient combined method of elution, struvite precipitation and on-line adsorption - Kejia Wu; Junxia Yu; Jia Wang; Xiaodi Li; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Journal of Water Process Engineering, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Applicability analysis of comprehensive drought index based on GRACE data in ten major river basins in China - Rong Wu; Zijun Wang; Chenfeng Cui; Yongxiang Li; Miao Tang; Jiangdong Chu; Renjie Xv; Chenrui Zhu; Shuo Wang; Yuli Li; Chengyuan Zhang; Zhannan Huang (Journal of Hydrology, 2024)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Secondary activation on plasma-activated water by plasma-treated cotton for restoring and enhancing disinfection effect - Zifeng Wang; Shenghang Xu; Xiangyu Wang; Dingxin Liu; Wanchun Li; Rusen Zhou; Qiuyi Yue; Pengfei Zhang; Jishen Zhang; Hao Zhang; Li Guo; Dandan Pei; et al. (Journal of Hazardous Materials, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Advancing mangrove species mapping: An innovative approach using Google Earth images and a U-shaped network for individual-level Sonneratia apetala detection - Chuanpeng Zhao; Yubin Li; Mingming Jia; Chengbin Wu; Rong Zhang; Chunying Ren; Zongming Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Analytical model of three-dimensional concentric ellipsoidal soil arching in geosynthetic-reinforced pile-supported embankments - Rong Sun; Xin Jiang; Lei Zhang; Canyang Cui; Zhengxian Li; Yanjun Qiu (Geotextiles and Geomembranes, 2024)

Soy protein isolate ameliorate gel properties by regulating the non-covalent interaction between epigallocatechin-3-gallate and myofibrillar protein - Ying Li; Yijun Zhang; Gongchen He; Ziyan Qiao; Rong Yang; Xi Zhou; Lin Chen; Xianchao Feng (Food Chemistry, 2024)

Responses of yield, CH4 and N2O emissions to ratoon rice cropping and different management practices - Haiyang Yu; Rong Zhu; Xuechen Zhang; Xiangtian Meng; Chao Kong; Guangbin Zhang; Xinhui Liu; Yaying Li; Yongxiang Yu; Huaiying Yao (Field Crops Research, 2024)

Temperature adaptive passive daytime radiative cooling: The impact of their essential properties on energy performance of different building types - Yujie Yang; Guoqiang Zhang; Li Rong (Energy and Buildings, 2024)

MOF-derived S, N co-doped porous carbon matrix with single Fe atoms and CoSx nanoparticles dual-sites for enhanced oxygen reduction - Yu chen; Jian Rong; Jing Wu; Yuzhe Zhang; Huaisheng Ao; Xudong Zheng; Chao Jing; Ruilan Yang; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2024)

Engineered multienzyme-mimicking 2D bismuthene catalytic nanotriggers enable cascade enzyodynamic-boosted and synergistic GPX4/FSP1-mediated ferroptosis amplification for cancer radiosensitization - Yipengchen Yin; Li Zhu; Tiaoyan Jiang; Rong Chai; Ya Zhang; Tianyu Li; Kai Wang; Sheng Wang; Qin Zhang (Chemical Engineering Journal, 2024)

Block copolymer nanoparticles doping polyacrylonitrile membranes for efficient adsorption of water-soluble dyes from water - Rong Cao; Enyang Zhang; Yuan Liu; Axiang Li; Wangqing Zhang (Chemical Engineering Journal, 2024)

Facile engineering of metal–organic framework derived SnO2@NiO core–shell nanocomposites based gas sensor toward superior VOCs sensing performance - Hui Xu; Haoran Zhong; Jinwu Hu; Xianjun Rong; Wenhui Zhang; Yinsheng Wang; Shengjuan Li; Guisheng Li; Ding Wang (Chemical Engineering Journal, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

Assessment of carbon emissions and reduction potential in China's copper smelting industry - Rong Gao; Yao Shi; Chun Cao; Huiquan Li; Yuanbo Xie; Jingjing Shi; Chenmu Zhang; Xue Guan (Journal of Industrial Ecology, 2024)
As the largest producer and consumer of copper, China is facing enormous challenges from carbon peaking and neutrality. This article adopts “bottom‐up” and “top‐down” methods to construct a more accurate model, to predict the CO 2 emissions of China's copper smelting industry, and explores its potential for carbon reduction in the future from three scenarios as the baseline scenario (BAU), the general low‐carbon (NLC), and the enhanced low‐carbon (ELC). The results show that the CO 2 emissions can achieve a peak in 2028 either in NLC or ELC scenarios, with a peak range of 14.9–16.88 million tonnes. Prior to reaching the peak, the contributions of energy adjustment, material substitution, and process selection to carbon reduction have significantly improved, and the contribution rates increased from 30.91%, 4.11%, and 1.46% to 42.7%, 32.07%, and 15.63% in ELC scenario. After the peak, the contribution of energy adjustment gradually slows down, while the material substitution continues to increase, and the contribution rates increased from 21.25% and 32.07% to 29.38% and 40.01% in NLC and ELC scenarios. In the future, concentrate oxygen‐enriched bottom‐blowing smelting and direct refining from waste copper anode furnaces show ideal potential for carbon reduction before 2025, increasing the proportion of recycled copper production, and adjusting energy structure will be more effective from 2025 to 2035. The conclusions of this study can provide a scientific basis for formulating policy recommendations for green and low‐carbon development of the copper industry in China and all over the world in the future.

Unraveling fertilization effects on the dynamics of arbuscular mycorrhizal fungal community in the Qinghai-Tibet Alpine Meadow - Longfei Liu; Yi Ren; Shuo Sun; Chen Liu; Kairui Ding; Rong Li; Pengfei Zhang; Biao Shen; Mohammadhossein Ravanbakhsh; Wu Xiong; Qirong Shen (Soil Ecology Letters, 2024)

Nitrifying and denitrifying microbes exhibit distinct community structure and activity responses to different crop rotation systems in subtropical paddy soils - Huifang Xu; Ke Li; Rong Sheng; Hongling Qin; Yi Liu; Anlei Chen; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Applied Soil Ecology, 2024)

Early Cretaceous mafic dikes in the eastern North China Craton: implications for the effect of slab subduction on the mantle sources - Chao Li; Lin Li; Ju-Quan Zhang; M. Santosh; Sheng-Rong Li; Bowen Wei; Cong Li (International Geology Review, 2024)

The change of environmental factors in the water near the Yangtze Estuary may induce the change of large yellow croaker fishery location there - Lina Cai; Jiahua Li; Xiaojun Yan; Rong Tang; Xinkai Zhang (Frontiers in Marine Science, 2024)
The large yellow croaker, an endemic migratory species in China’s coastal waters, holds considerable economic importance. It is very necessary and significant to study the spatio-temporal evolution of large yellow croaker fishery based on environmental factors. In this paper, the HY-1C/D Coastal Zone Imager was applied to reveal distributional details of suspended sediment concentration and chlorophyll-a concentration in large yellow croaker fishery. Furthermore, combined with multi-source data, the characteristics of other environmental parameters such as temperature, salinity, current, wind and fronts were analyzed to reveal the changing of large yellow croaker fishery location. The results show that: (1) The environmental factors of large yellow croaker fishery exhibit pronounced spatial and temporal characteristics. Generally, the temperature (9-28°C), salinity (20-34 ‰) and other water environmental factors of the fishing ground are conducive to the survival and growth of large yellow croaker. The formation and change of fishery are closely related to environmental factors in the water. (2) The change of environmental factors in the water may induce the change of large yellow croaker fishery location. Winter sea surface temperature has significantly risen over the past two decades (2004-2023). With the sea surface temperature rising by approximately 2°C west of 125°E, the overwintering ground has expanded westward, increasing by nearly 29%. In addition, the scale and number of offshore windmills increased by 836% and 456% respectively over the decade (2013-2023). In 2023, offshore wind farms cover an area of 145.47 km 2 and have 200 windmills. Wind turbine piles resembling artificial reefs. It can not only promote the waters vertical exchange to enhance the nutrients in upper waters but also provide a protective base for fish spawning. Thus, effectively attracting fish species. The construction of offshore wind farms has extended spawning ground north-westward to the mouth of the Yangtze River Estuary, expanding by nearly 21%. This study improved the cognition level of resources, habitat environment and change trend of large yellow croaker. It also provided technical support for the construction and protection of the large yellow croaker fishery.

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Performance of a novel annular electric field membrane bioreactor and its membrane fouling control in treating catering wastewater - Rong Zhang; Mengqian Li; Huan Ma; Yanyan Wang; Beiyu Xin; Jifeng Guo (Chemosphere, 2024)

Changes in secondary sexual characteristics of female red swamp crayfish (Procambarus clarkii) and relationship to ovarian development: Implications for intensive breeding of seedlings - Lirong Qin; Jinhui He; Kuan Rong; Chao Guo; Jiashou Liu; Tanglin Zhang; Wei Li (Aquaculture, 2024)

Experimental study on temperature difference between the interior and exterior of the vehicle transporting weaner pigs - Guoxing Chen; Cecilie Kobek-Kjeldager; Line D. Jensen; Jens K. Kristensen; Marianne Kaiser; Karen Thodberg; Guoqiang Zhang; Li Rong; Mette S. Herskin; Leslie Foldager (Biosystems Engineering, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

The positive role of pyrite in anammox performance and granulation - Huiying Sui; Baoyong Zhang; Zunqing Wen; Nianbo Zhang; Na Zhang; Ruiyan Zhang; Zengjin Li; Rong Xue (Journal of Water Process Engineering, 2024)

Spatial and temporal dynamics of microbes and genes in drinking water reservoirs: Distribution and potential for taste and odor generation - Xuanzi Zhangsun; Honghong Guo; Quanjie Du; Na Li; Shuhong Xue; Rong Li; Wenrui Ma; Xiang Liu; Haihan Zhang; Tinglin Huang (Journal of Hazardous Materials, 2024)

Novel photic responsive Janus nanoparticles: Interfacial catalysts for efficient preparation of biodiesel - Mingshu Li; Rong Zhang; Chuanxing Jia; Zhongqiu Liu; Yujing Liu; Anguo Ying (Fuel, 2024)

Improving curcumin bioavailability: Targeted delivery of curcumin and loading systems in intestinal inflammation - Junyi Zhao; Wei Jia; Rong Zhang; Xin Wang; Li Zhang (Food Research International, 2024)

Investigation of isomerization and oxidation of astaxanthin in ready-to-eat Litopenaeus vannamei during accelerated storage - Na Li; Xin Fan; Yefan Wang; Kexin Zhang; Rong Liu; Yunpeng Xu; Zhifeng Tan; Wensi Xu; Dayong Zhou; Deyang Li (Food Research International, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Simple theranostics nanoagent for precision suppression of tumor growth and metastasis: A traditional fermented product having a novel functional breakthrough - Pengmin Liu; Rong Dai; Juan Li; Lin Chen; Qi Liu; Yuhang Wang; Shichao Meng; Binyue Zhang; Jinxuan Li; Weiwei Kang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Controlled assembly and synthesis of oxygen-deficient W18O49 films based on solvent molecular strategy for electrochromic energy storage smart windows - Xiaohui Sun; Wei Wu; Nana Liu; Peng Li; Xueying Zhao; Zhaozhu Qu; Kunming Zhao; Bo Wang; Xianhui Rong; Xuyang Zhang; Guohua Wu; Xiangwei Wang (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Bioactives from biomass: Treasure for future potent antimicrobial applications - Weicheng Chen; Peng Zhang; Yucui Ding; Xiaobin Xie; Jianlong Fu; Rong Zhao; Yihan Xiao; Miodrag J. Lukic; Bin Li; Weishan Wang; Song Chen (Chemical Engineering Journal, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Biological exposure to microplastics and nanoplastics and plastic additives: impairment of glycolipid metabolism and adverse effects on metabolic diseases - Peng Chen Zheng; Rong Li; Keng Po Lai; Xiao Xi Zhang (Environmental Science and Pollution Research, 2024)

Recent research and development of individual precision cooling systems for dairy cows – A review - Wenqi Zhang; Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kaiying Wang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Effects of microplastics derived from biodegradable mulch film on different plant species growth and soil properties - Rong Liang; Chi Zhang; Ruifang Zhang; Qingyun Li; Hongquan Liu; Xin-Xin Wang (Science of The Total Environment, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

Late Holocene rapid paleoenvironmental changes and anthropogenic impacts in central Yunnan, southwest China - Zhikai Xue; Weiwei Sun; Beibei Shen; Rong Wang; Chunhai Li; Enlou Zhang (Quaternary International, 2024)

Interactions between fibroblasts and monocyte-derived cells in chronic lung injuries induced by real-ambient particulate matter exposure - Youjin Zeng; Rui Zhang; Yue Jiang; Daochuan Li; Liping Chen; Guanghui Dong; Rong Zhang; Yujie Niu; Wen Chen; Shen Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Elemental and isotopic perspective on the formation of Permian mafic magmatic rocks from the Xing'an Mongolia Orogenic Belt and northern North China Craton - Wei Liu; Dongya Zou; Xiaolong Zhang; Xiaoyan Gu; Rong Xu; Gangzhu Li (Lithos, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Pollution area identification, receptor model-oriented sources and probabilistic health hazards to prioritize control measures for heavy metal management in soil - Ram Proshad; S.M. Asharaful Abedin Asha; Md Anwarul Abedin; Geng Chen; Ziyi Li; Shuangting Zhang; Rong Tan; Yineng Lu; Xifeng Zhang; Zhuanjun Zhao (Journal of Environmental Management, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Modeling of activated carbon and multi-scale molecular simulation of its water vapor adsorption: A review - Zhongfan Mo; Ming Li; Shengnan Sun; Rong Zhu; Danya Zhan; Aimin Li; Yinning Li; Ying Zhang; Qiongfen Yu (Journal of Environmental Chemical Engineering, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

Identification of peptides from Corneum Galli Gigeri Endothelium and inhibiting H2O2-induced gastric mucosa associated with the Rho signaling pathway - Rong xiang Guo; Huiying Zhang; Yao Chen; Pan Li; Bing Du (Food Bioscience, 2024)

Effects of co-assembly of gliadin and carboxymethyl cellulose on the high internal phase pickering emulsions: Rheology properties, 3D printing performance and oil-soluble nutrient delivery - Duo Zhang; Yongkang Yang; Rixin Li; Xing Rong; Wenli Zhang; Miao Zhang; Bin Li; Xuan Zhang (Food Hydrocolloids, 2024)

Mining of novel target genes through Pan-genome analysis for Conventional PCR and Real-Time PCR detection of Staphylococcus argenteus in food - Jiahui Huang; Jingsha Dai; Ming Liu; Shixuan Huang; Yuwei Wu; Dongli Rong; Yuanyu Li; Miao Zhao; Ying Li; Jumei Zhang; Shi Wu; Qingping Wu (Food Control, 2024)

PoIL8-L, a teleost interleukin-8 like, enhances leukocyte cellular vitality and host defense against bacterial infections in Japanese flounder (Paralichthys olivaceus) - Kun-yu Zhao; Yue Fang; Rong-jing Xu; Jian Zhang; Bin Sun; Xue-peng Li (Fish & Shellfish Immunology, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

On-demand detachable and reuseable adhesives assembled by organic-silicon nanogels with wide applicability and excellent harsh-environment resistance - Hui Rong; Pengwei Zhao; Manhua Lu; Liandong Deng; Shuangyang Li; Xiaobin Fan; Zhanpeng Ye; Jianhua Zhang; Anjie Dong (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Low oxygen adsorption energy barrier architectures to facilitate microenvironmental photocatalytic disinfection in Wei River - Lenan Yao; Yunyan Bai; Li Ding; Yayun Hu; Zuwang Zhang; Yajie Zhang; Rui Chen; Haijiao Xie; Jianlong Wang; Rong Wang (Chemical Engineering Journal, 2024)

Accelerated cartilage regeneration through immunomodulation and enhanced chondrogenesis by an extracellular matrix hydrogel encapsulating Kartogenin - Kai Huang; Qing-Yi Zhang; Jie Tan; Rong Nie; Zi-Yuan Feng; Yuan Liu; Ning Sheng; He-Xi Li; Yue-Qi Zhang; Bin Shen; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Tuning oxygen vacancies via photoinduced defect engineering in plasma pre-treated TiO2 for efficient solar-light-driven oxidation of trace methane - Qiyu Zhang; Jiakang Duan; Zhiping Zhu; Li Rong; Xiaochang Lin; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2024)

Quantifying the biodiversity and ecosystem service outcomes of karst ecological restoration: A meta-analysis of South China Karst - Yue Chen; Cai Cheng; Kangning Xiong; Li Rong; Shihao Zhang (CATENA, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Investigating protistan predators and bacteria within soil microbiomes in agricultural ecosystems under organic and chemical fertilizer applications - Chen Liu; Zeyuan Zhou; Shuo Sun; Qi Zhang; Shiqi Sun; Xinnan Hang; Mohammadhossein Ravanbakhsh; Zhong Wei; Rong Li; Shimei Wang; Wu Xiong; George A. Kowalchuk; et al. (Biology and Fertility of Soils, 2024)
Organic farming can enhance biodiversity and soil health and is a sustainable alternative to conventional farming. Yet, soil protists especially protistan predators, have received inadequate attention, and their contributions to the sustainability of organic farming remained underexplored. In this study, we examined soil microbial communities from 379 samples, including both organic and chemically fertilized soils from China. Our findings revealed higher bacterial diversity and increases in plant-beneficial bacteria in organically farmed soils. Notably, organic farming systems facilitated dynamic predator-prey interactions, which may be disrupted by the application of chemical fertilizers. Additionally, organic farming enriched protistan predators, enhancing the relative abundance of functional PGPR, thus improving soil health. We further conducted a case study highlighting the critical role of organic matter in sustaining protistan predator populations and their interactions with bacteria. We propose the crucial contributions of organic inputs for supporting protistan predators and the interplay of predator-prey, ultimately enhancing soil functions and promoting agricultural sustainability.

Dual colorimetric platforms for direct detection of glyphosate based on Os-Rh nanozyme with peroxidase-like activity - Yingying Zhong; Junsong Yang; Wanying Wu; Haoyang Chen; Shuwei Li; Ziying Zhang; Shicheng Rong; Hongwu Wang (Analytica Chimica Acta, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

Sequential Two-Mode Fusion Underwater Single-Photon Lidar Imaging Algorithm - Tian Rong; Yuhang Wang; Qiguang Zhu; Chenxu Wang; Yanchao Zhang; Jianfeng Li; Zhiquan Zhou; Qinghua Luo (Journal of Marine Science and Engineering, 2024)
Aiming at the demand for long-range and high-resolution imaging detection of small targets such as submerged submarine markers in shallow coastal waters, research on single-photon lidar imaging technology is carried out. This paper reports the sequential two-mode fusion imaging algorithm, which has a strong information extraction capability and can reconstruct scene target depth and reflection intensity images from complex signal photon counts. The algorithm consists of four steps: data preprocessing, extremely large group value estimation, noise sieving, and total variation smoothing constraints to image the target with high quality. Simulation and test results show that the imaging performance and imaging characteristics of the method are better than the current high-performance first-photon group imaging algorithm, indicating that the method has a great advantage in sparse photon counting imaging, and the method proposed in this paper constructs a clear depth and reflectance intensity image of the target scene, even in the 50,828 Lux ambient strong light and strong interference, the 0.1 Lux low-light environment, or the underwater high-attenuation environment.

Numerical Analysis of Leading-Edge Roughness Effects on the Aerodynamic Performance of a Thick Wind Turbine Airfoil - Wei Zhang; Kuichao Ma; Chang Cai; Xiangyu Sun; Jun Zhang; Xiaohui Zhong; Xiaomin Rong; Qing’an Li (Journal of Marine Science and Engineering, 2024)
The aerodynamic performance of wind turbine airfoils is crucial for the efficiency and reliability of wind energy systems, with leading-edge roughness significantly impacting blade performance. This study conducts numerical simulations on the DU 00-W-401 airfoil to investigate the effects of leading-edge roughness. Results reveal that the rough airfoil exhibits a distinctive “N”-shaped lift coefficient curve. The formation mechanism of this nonlinear lift curve is primarily attributed to the development of the trailing-edge separation vortex and variations in the adverse pressure gradient from the maximum thickness position to the trailing-edge confluence. The impact of different roughness heights is further investigated. It is discovered that when the roughness height is higher than 0.3 mm, the boundary layer can be considered fully turbulent, and the lift curve shows the “N” shape stably. When the roughness height is between 0.07 mm and 0.1 mm, a transitional state can be observed, with several saltation points in the lift curve. The main characteristics of different flow regimes based on different lift curve segments are summarized. This research enhances the understanding of the effects of leading-edge roughness on the aerodynamic performance of a thick wind turbine airfoil, and the simulation method for considering the effect of leading-edge roughness is practical to be applied on large-scale wind turbine blade to estimate the aerodynamic performance under rough leading-edge conditions, thereby supporting advancements in wind turbine technology and promoting the broader adoption of renewable energy.

Research progress on hepatotoxicity mechanism of polygonum multiflorum and its main components - Liping Gong; Xianhui Shen; Nana Huang; Kaiyi Wu; Rongrong Li; Ying Liu; Huijie Zhang; Siyi Chen; Rong Sun (Toxicon, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Genetic variation in a heat shock transcription factor modulates cold tolerance in maize - Lei Gao; Lingling Pan; Yiting Shi; Rong Zeng; Minze Li; Zhuoyang Li; Xuan Zhang; Xiaoming Zhao; Xinru Gong; Wei Huang; Xiaohong Yang; Jinsheng Lai; et al. (Molecular Plant, 2024)

p‑Phenylenediamine antioxidants in PM2.5: New markers for traffic in positive matrix factorization source apportionment - Nan Jiang; Xuexin Hao; Zichen Wang; Minzhen Li; Dong Zhang; Rong Cao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Hazardous Materials, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Constructing direct Z-scheme heterojunction of NiCo-LDH coated with g-C3N4 for boosting photocatalytic H2 evolution - Qinyi Gu; Chujun Feng; Congtian Liu; Jian Rong; Yuzhe Zhang; Xudong Zheng; Zhongyu Li; Song Xu (Fuel, 2024)

Enzymatically green-produced bacterial cellulose nanoparticle-stabilized Pickering emulsion for enhancing anthocyanin colorimetric performance of versatile films - Shiqi Li; Rong Liu; Jiale Zhao; Shuo Zhang; Xuerong Hu; Xingnan Wang; Zhenpeng Gao; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Chemistry, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Microplastics footprint in nature reserves-a case study on the microplastics in the guano from Yancheng Wetland Rare Birds National Nature Reserve, China - Huimin Jiang; Hai Cheng; Shiyue Wu; Hongshan Li; Hao Chen; Zhenghao Li; Xinyun Yao; Yanan Zhang; Yaqin Chen; Shuyi Chen; Shihao Chen; Liang Zheng; et al. (Environmental Research, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

Gypsum ridges as conduits for deep methane emission in an evaporite basin– Insights into the origin of atmospheric methane on Mars - Yiliang Li; Zikang Li; Xiaorong Qin; Binlong Ye; Ziyu Niu; Anouk Ehreiser; Wenhua Zhang; Yang Pan; Liping Qin; Rong Shu; Jianxi Zhu; Yigang Xu; et al. (Earth and Planetary Science Letters, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

Ti2TaC2: A novel out-of-plane ordered MXene towards flexible and cytocompatible supercapacitors - Yunfeng Guan; Lixian Jiang; Rong Zhao; Xuanke Li; Hui Zhu; Qin Zhang; Zhijun Dong; Nianjun Yang; Ye Cong (Chemical Engineering Journal, 2024)

Difunctional POM-based artificial leaf with directed charge transfer to promote photosynthetic overall reaction - Huafeng Li; Yanan Qu; Jiayi Zhang; Kang Bu; Shiliang Heng; Shanshan Zhang; Jianzhong Guo; Bing Li; Rong Wan; Pengtao Ma; Liqun Bai (Chemical Engineering Journal, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Superwetting MAX@SiO2 coatings with high photothermal conversion performances for efficient seawater desalination and anti-/de-icing - Helong Zhang; Chuxiong Qiu; Rong Zhang; Hao Zhang; Yunxia Chen; Tao Zeng; Fen Qiao; Lee Li; Ghafar Ali; Xiujian Zhao; Yi Xie (Chemical Engineering Journal, 2024)

A twin S-scheme CoFe2O4/VCNDA/BiVO4 nanozyme for photo-auto-enzyme-coupled catalytic degradation of carbamazepine - Chujun Feng; Qinyi Gu; Jian Rong; Xudong Zheng; Yuzhe Zhang; Qian Liang; Zhongyu Li; Song Xu (Chemical Engineering Journal, 2024)

Nitrogen removal performance and mechanism in constructed wetlands under saline conditions: Role of Canna indica inoculated with Piriformospora indica - Naxin Cui; Min Cai; Xu Zhang; Rong Zeng; Li Zhou; Guifa Chen; Guoyan Zou (Bioresource Technology, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

The gut microbiome: an important role in neurodegenerative diseases and their therapeutic advances - Songlin Li; Linna Zhao; Jie Xiao; Yuying Guo; Rong Fu; Yunsha Zhang; Shixin Xu (Molecular and Cellular Biochemistry, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Protist communities as indicators of fertilization-induced changes in a species-rich grassland ecosystem - Shuo Sun; Alexandre Jousset; Stefan Geisen; Enrique Lara; Pengfei Zhang; Rong Li; Francisco Dini-Andreote; Mohammadhossein Ravanbakhsh; Qirong Shen; George A. Kowalchuk; Wu Xiong (Agriculture, Ecosystems & Environment, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Dietary anthocyanins as natural phytochemicals for regulating hyperuricemia: Proposed intestinal flora, key enzyme activity, and anti-inflammatory pathways - Shuai Lv; Wei Jia; Rong Zhang; Li Zhang (Trends in Food Science & Technology, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

In-situ electric swing adsorption enabling superior water vapor capture of salt-based carbon fibers - Rong Zhu; Yaowei Huang; Qiongfen Yu; Ming Li; Yunfeng Wang; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Regulatory mechanisms of biochar alleviating ammonia inhibition to methanogenesis during long-term operation of anaerobic membrane bioreactor treating swine wastewater - Bo Zhang; Gaojun Wang; Xiang Zhang; Peng Fu; Lu Chen; Yizhi Chen; Qian Li; Rong Chen (Chemical Engineering Journal, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Degradation of wild fruit forests created less diverse and diffuse bacterial communities decreased bacterial diversity, enhanced fungal pathogens and altered microbial assembly in the Tianshan Mountain, China - Xiaoying Rong; Nan Wu; Benfeng Yin; Xiaobing Zhou; Bingjian Zhu; Yonggang Li; Zachary T. Aanderud; Yuanming Zhang (Plant and Soil, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

The immunosuppressive landscape in tumor microenvironment - Wuyi Liu; Huyue Zhou; Wenjing Lai; Changpeng Hu; Rufu Xu; Peng Gu; Menglin Luo; Rong Zhang; Guobing Li (Immunologic Research, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Integrated Information for Pathogenicity and Treatment of Spiroplasma - Yixue You; Jianmin Xiao; Jiaxin Chen; Yuxin Li; Rong Li; Siyuan Zhang; Qichen Jiang; Peng Liu (Current Microbiology, 2024)

Microneedle electrochemical sensor based on disposable stainless-steel wire for real-time analysis of indole-3-acetic acid and salicylic acid in tomato leaves infected by Pst DC3000 in situ - Lingjuan Tang; Daodong Li; Wei Liu; Yihui Tang; Rongcheng Zhang; Yiran Tian; Rong Tan; Xiaolong Yang; Lijun Sun (Analytica Chimica Acta, 2024)

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

Assessment of spray nozzles on water distribution on cow’s surface and efficiency of water utilization by CFD - Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2024)

Genomic analysis of Clostridium perfringens type D isolates from goat farms - Hang Feng; Ke Wu; Yuan Yuan; Mingjin Fang; Juan Wang; Ruichao Li; Rong Zhang; Xinglong Wang; Dongyang Ye; Zengqi Yang (Veterinary Microbiology, 2024)

MicroRNA expression profile of chicken liver at different times after Histomonas meleagridis infection - Qiaoguang Chen; Yuming Zhang; Jie Rong; Chen Chen; Shuang Wang; Jiege Wang; Zaifan Li; Zhaofeng Hou; Dandan Liu; Jianping Tao; Jinjun Xu (Veterinary Parasitology, 2024)

Intelligent DNA-based hydrogels: An outstanding programable and biocompatible material for food applications - Guo Li; Hao Huang; Liang Zou; Xiaochen Zhang; Xingyu Lin; Miral Javed; Xingcai Zhang; Yanqun Xu; Rong Ai; Zisheng Luo; Dong Li (Trends in Food Science & Technology, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

Efficient removal of the residual ammonium from weathered crust elution-deposited rare earth tailings by a ternary compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Rong Wang; Fang Zhou; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2024)

Inactivation of Aeromonas hydrophila in water by dielectric barrier discharge plasma: Efficiency, mechanism, and application safety - Le Wang; Zhenfei Zhu; Pengcheng Yan; Rong Zhang; Min Zhang; Xiangyu Wang; Guangzhou Qu; Tiecheng Wang; Ronghua Li (Journal of Water Process Engineering, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Divergent impacts of fertilization regimes on below-ground prokaryotic and eukaryotic communities in the Tibetan Plateau - Shuo Sun; Chen Liu; Yun Zhang; Yang Yue; Shiqi Sun; Yang Bai; Pengfei Zhang; Mohammadhossein Ravanbakhsh; Francisco Dini-Andreote; Rong Li; Zhenhua Zhang; Alexandre Jousset; et al. (Journal of Environmental Management, 2024)

Enhanced waste Plastics-to-Power in situ conversion through iron oxide as pseudofuel in solid oxide fuel cells - Rong Zhang; Wenting An; Yanxia Guo; Yong Jiao; Si-Dian Li; Fangqin Cheng (Fuel, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Fluoride exposure during puberty induces testicular impairment via ER stress-triggered apoptosis in mice - Rong Wang; Wenjing Gong; Yumeng Jiang; Qizi Yin; Ziyue Wang; Jie Wu; Mingming Zhang; Mengyuan Li; Yehao Liu; Juan Wang; Yuanhua Chen; Yanli Ji (Food and Chemical Toxicology, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

“Edge in-situ heterogeneous” BiOI based on defect engineering and non-noble metal deposition: Boosting visible-light photocatalytic sterilization - Bangfeng Fu; Yifan Pan; Peng Zhao; Liang Zhang; Junchen Zhuo; Jianxing Feng; Bingzhi Li; Lenan Yao; Jiafeng Xi; Xi Lan; Linpin Luo; Ting Du; et al. (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Multiple Applications of a Novel Fluorescence Probe with Large Stokes Shift and Sensitivity for Rapid H2S Detection - Lai-Xin Hong; Le Sun; Cong Li; Rong-Lan Zhang; Jian-She Zhao (Journal of Fluorescence, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Strong ground motion characteristics of the 2022 MW 6.6 Luding earthquake and regional variability in ground motion among three earthquake areas in Sichuan, Southwest China - Bin Zhang; Xiaojun Li; Yanxiang Yu; Xiaojian Lu; Mianshui Rong; Su Chen; Zhao An; Zhenghui Xiong (Bulletin of Earthquake Engineering, 2024)

Drought reduces peanut yield indirectly through regulating soil nematode community in a manipulative field experiment in central China - Cancan Zhao; Rong Fan; Xiaolin Li; Like Fan; Liwei Zhang; Xinyu Yan; Xiang Zhao; Yuan Miao; Yanfeng Sun; Yuanhu Shao; Guoyong Li; Shenglei Fu (Applied Soil Ecology, 2024)

A polyfunctionalized carbon framework composite for efficient decontamination of Cr(VI) and polycyclic aromatic nitrides from acidic wastewater - Weilong Wu; Han Zhang; Rong Qian; Kunru Yu; Ronghua Li; Kuok Ho Daniel Tang; Xuan Wu; Zhiqiang Guo; Cong Shao; Feixue Yue; Zengqiang Zhang (Environmental Science and Pollution Research, 2024)

Multiple scenario land use simulation based on a coupled MOGA-PLUS model: a case of the Yellow River Basin - Guanghui Li; Yinghui Chang; Pengyan Zhang; Qianxu Wang; Zhuo Chen; Xinyue Zhang; Guangrui Xing; Rong Lu; Mengfan Li; Lei Gu (Environmental Science and Pollution Research, 2024)

NCOA4-mediated ferritinophagy participates in cadmium-triggered ferroptosis in spermatogonia - Didi Jia; Mingming Zhang; Mengyuan Li; Wenjing Gong; Wei Huang; Rong Wang; Yihang Chen; Qizi Yin; Jie Wu; Zhongxiu Jin; Juan Wang; Yehao Liu; et al. (Toxicology, 2024)

Long-term chemical and organic fertilization induces distinct variations of microbial associations but unanimous elevation of soil multifunctionality - Ke Li; Anlei Chen; Rong Sheng; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Science of The Total Environment, 2024)

Centennial-scale cooling-induced megadroughts in Myanmar's tropical arid region over the past 8000 years - Jie Li; Jiaoyang Zhang; Jingjing Li; Miaofa Li; Jixiang Liu; Bob Hudson; Kyaing Sein; Huiling Zhang; Rong Wang; Luo Wang; Guoqiang Chu; Jule Xiao (Quaternary Science Reviews, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Multistage dolomitization influenced by the Emeishan large igneous province: Petrographical and geochemical evidence - Yang Li; Xiyan Yang; Xinzhi Wang; Cunhui Fan; Xiangyu Fan; Yu Zhang; Rong Yang; Yue Li; Zisang Huang; Fei Huo (Marine and Petroleum Geology, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Metabolome and transcriptome reveal high abundance of bioactive substances in albino jujube fruit as potential function food - Yang Wang; Yong Huang; Panhui Song; Xuemei Peng; Xinyu Li; Rong Su; Hui Zhang; Lijin Lin; Hui Xia; Qunxian Deng (Food Bioscience, 2024)

Effects of carnosine combined with Lactobacillus on the antioxidant capacity of liver and kidney in normal or stressed mice - Jian Qin; Yue Ma; Conghui Wang; Huiying Li; Zhiqiang Zou; Yunqing Zhang; Jing Ma; Rong Du (Food Bioscience, 2024)

Effects of dietary supplementation with green lentil (Lens culinaris) hulls on NAFLD: Focus on intestinal and hepatic metabolism - Fanghua Guo; Dongying Chen; Rong Tsao; Fereidoon Shahidi; Hua Xiong; Hua Zhang; Li Jiang; Yong Sun (Food Bioscience, 2024)

Prospective findings from the Dongfeng-Tongji cohort: Exposure to various metals, the expression of microRNA-4286, and the incidence of acute coronary syndrome - Miaoyan Shen; Xuedan Xu; Wending Li; Xi Wang; Rong Peng; Xuezhen Liu; Qiuhong Wang; Xiaomin You; Pinpin Long; Hao Wang; Rundong Niu; Yu Yin; et al. (Environmental Research, 2024)

Role of phytoliths in carbon stabilization of Zostera marina L. plants: One unreported mechanism of carbon sequestration in eelgrass beds - Bowen Rong; Li Zhang; Zhaojun Liu; Weihao Bai; Weidong Gu; Xiangtao Wei; Wenhao Hou; Changzi Ge (Estuarine, Coastal and Shelf Science, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

CsSHMT3 gene enhances the growth and development in cucumber seedlings under salt stress - Zhuohui Zhang; Xuemei Hou; Rong Gao; Yihua Li; Zhiqi Ding; Yi Huang; Kangding Yao; Yandong Yao; Cheng Liang; Weibiao Liao (Plant Molecular Biology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

Analysis of mild and severe neonatal enterovirus infections in a Chinese neonatal tertiary center: a retrospective case-control study - Junshuai Li; Jingjing Xie; Min Zhang; Zhuojun Xiao; Fan Zhang; Weiqing Huang; Yong Zhou; Weiqun Yan; Rong Zhang; Xiaoming Peng (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Exogenous carbon addition soil mediated phosphorus dynamics under eight years continuous input of swine manure in a wheat-rice rotation - Chunlong Zhang; Xiaoyan Tang; Changquang Wang; Edith le Cadre; Rong Huang; Qi Tao; Yingjie Wu; Youlin Luo; Qiang Xu; Genchuan Bai; Bing Li (Agriculture, Ecosystems & Environment, 2024)

Index construction and real-time hazard assessment of rice sterile-type chilling injury process in Northeast China - Bilige Sudu; Kaiwei Li; Suri Guga; Teri Gele; Feng Zhi; Ying Guo; Sicheng Wei; Guangzhi Rong; Yongbin Bao; Xingpeng Liu; Jiquan Zhang (Agricultural and Forest Meteorology, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

CFD investigation on a novel pen partition-attached jet air supply for mitigating heat stress among lactating sows - Guoxing Chen; Guoqiang Zhang; Bjarne Bjerg; Poul Pedersen; Torben Jensen; Li Rong (Computers and Electronics in Agriculture, 2024)

Piped-slow-release calcium nitrate dosing: A new approach to in-situ sediment odor control in rural areas - Yongchun Zhang; Ziyang Liang; Peiling Li; Jiangtian Lai; Peilun Kang; Rong Huang; Yuhai Liang; Guangwei Yu (Science of The Total Environment, 2024)

Advances in understanding bioaerosol release characteristics and potential hazards during aerobic composting - Sai Yang; Yanan Yin; Wenrong Zhang; Haichao Li; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2024)

Effects of typhoon events on coastal hydrology, nutrients, and algal bloom dynamics: Insights from continuous observation and machine learning in semi-enclosed Zhanjiang Bay, China - Peng Zhang; Huizi Long; Zhihao Li; Rong Chen; Demeng Peng; Jibiao Zhang (Science of The Total Environment, 2024)

Massive early Middle Pleistocene cheetah from eastern Asia shed light onto the evolution of Acinonyx in Eurasia - Qigao Jiangzuo; Yaming Wang; Joan Madurell-Malapeira; Saverio Bartolini Lucenti; Shijie Li; Shiqi Wang; Zhaoyu Li; Rong Yang; Yi Jia; Lu Zhang; Shanqin Chen; Changzhu Jin; et al. (Quaternary Science Reviews, 2024)

The separate and synergistic role of biochar and electric field to facilitate mesophilic anaerobic digestion of food waste slurry - Gaojun Wang; Bo Zhang; Changxi Sun; Lu Chen; Kexin Wang; Qian Li; Rong Chen (Journal of Water Process Engineering, 2024)

Development of a novel DGT passive sampler for measuring polycyclic aromatic hydrocarbons in aquatic systems - Qiuyu Rong; Yanying Li; Jun Luo; Liying Yan; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Enhanced atomic H* utilization on urchin-like TiO2-supported palladium nanoparticles for efficient electrocatalytic detoxification of chlorinated organics - Jun Zhang; Shuyue Liu; Shiyu Lu; Chunyuan Wang; Pingjuan Liang; Huan Yi; Mengjie Li; Laizheng Luo; Rong Wang; Guangming Jiang (Fuel, 2024)

Modifying duck myofibrillar proteins using sodium bicarbonate under cold plasma treatment: Impact on the conformation, emulsification, and rheological properties - Shengqi Jiang; Chunjie Yang; Rong Bai; Ziwei Li; Linlu Zhang; Ya Chen; Xiang Ye; Siying Wang; Hao Jiang; Wu Ding (Food Hydrocolloids, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

Expression analysis and antiviral activity of koi carp (Cyprinus carpio) viperin against carp edema virus (CEV) - Xiao-wen Wang; Rong Zhang; Li-li Liu; Hui-juan Li; Hua Zhu (Fish & Shellfish Immunology, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

NiCoP cocatalyst modified g-C3N4 as ohmic junction photocatalyst for efficient degradation of tetracycline under visible light - Qinyi Gu; Chujun Feng; Jian Rong; Yuzhe Zhang; Xudong Zheng; Jinfeng Mei; Zhongyu Li; Song Xu (Environmental Research, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Multiple stimulus responsive of a novel naphthalenediimide-based 2D alkaline-earth metal MOF material: Hydrochromism, amine-/acid-induced chromism and ionochromism as well as visual artificial film application - Rong Huo; Ting Zhang; Li Xian Sun; Li Na Zhao; Yong Heng Xing; Feng Ying Bai (Chemical Engineering Journal, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Ceria nanoparticles: biomedical applications and toxicity - Xiaoxuan Fu; Peng Li; Xi Chen; Yuanyuan Ma; Rong Wang; Wenxuan Ji; Jiakuo Gu; Bowen Sheng; Yizhou Wang; Zhuhong Zhang (Journal of Zhejiang University-SCIENCE B, 2024)

Atmospheric responses to the interannual variability of sea surface temperature front in the summertime Southern Ocean - Qian-Rong Rao; Li Zhang; Xuya Ren; Lixin Wu (Climate Dynamics, 2024)
Air–sea interactions in mid-latitudes and their climatic effects have long been a research focus. However, the influence of the variability of the Southern Oceanic Front (SOF) on atmospheric processes at interannual timescales remains somewhat ambiguous from existing studies. Using reanalysis data, our findings reveal that the SOF reaches its maximum intensity during the austral summer, characterized by pronounced interannual variability and an insignificant trend. On the one hand, an enhanced SOF intensifies the meridional temperature gradient and atmospheric baroclinicity, accompanied by increased local and downstream baroclinic energy conversion. This amplifies storm track activities in both the lower and upper troposphere. On the other hand, the atmospheric circulation in mid- and high-latitudes exhibits an equivalent barotropic response. This is attributed to the feedback of storm tracks on the mean flow, dominated by the transient eddy vorticity forcing. Moreover, we compare the relative contributions of the South Indian Oceanic Front (SIOF) and South Atlantic Oceanic Front (SAOF) variability to storm track and atmospheric circulation. Results indicate that the SIOF variability dominates the downstream development of storm track response and modulates the anomalous atmospheric circulation around the Antarctic, while the SAOF variability produces only a limited local atmospheric response.

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part I: mean state - Zhen Fu; Yi Zhang; Xiaohan Li; Xinyao Rong (Climate Dynamics, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

PBA alleviates cadmium-induced mouse spermatogonia apoptosis by suppressing endoplasmic reticulum stress - Rong Wang; Mengyuan Li; Zhen Wu; Wenjing Gong; Mingming Zhang; Yehao Liu; Yuyou Yao; Yanli Ji (Toxicology in Vitro, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

Analysis of the transmission chain of carbapenem-resistant Enterobacter cloacae complex infections in clinical, intestinal and healthcare settings in Zhejiang province, China (2022–2023) - Zelin Yan; Xiaoyang Ju; Yanyan Zhang; Yuchen Wu; Yi Sun; Panfeng Xiong; Yan Li; Ruichao Li; Rong Zhang (Science of The Total Environment, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

An integrated calibration strategy for the development and validation of an LC-MS/MS method for accurate quantification of egg allergens (Gal d 1–6) in foods - Shupeng Yang; Jingjing Chen; Mohamed F. Abdallah; Haopeng Lin; Peijie Yang; Jianxun Li; Rong Zhang; Qianqian Li; Peng Lu; Shuyan Liu; Yi Li (Food Chemistry, 2024)

Biochar-mediated synergistic promotion of DIET and IHT: Kinetic and thermodynamic insights into propionate two-step syntrophic methanogenesis - Danyang Zhao; Peiyun Zhang; Yaqian Liu; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Coculture of Chlorella protothecoides and Coccomyxa subellipsoidea enhances cell growth and lipid accumulation: An effective strategy for biodiesel production - Yuqin Li; Yuanyuan Luo; Rong Zhou; Xiaohong Zuo; Yong Zhang; Zhenyao Wang; Xuan Li; Xing Zhang; Zihao Qin; Carol Sze Ki Lin (Chemical Engineering Journal, 2024)

A robust Zr(IV)-based metal-organic framework featuring high-density free carboxylic groups for efficient uranium recovery - Bin Wang; Chunyu Bao; Jiahui Xu; Yunnan Tao; Long Chen; Duo Zhang; Kui Tan; Shuao Wang; Jian-Rong Li; Shengqian Ma (Chemical Engineering Journal, 2024)

In-situ GSH-responsive gas nanogenerator for active NIR-II FL/PA imaging and synergistic restoration the macrophage niche in rheumatoid arthritis - Xiaochun Zheng; Weiwei Kang; Yarong Jin; Xin Zhang; Wenxuan Wang; Dongsheng Li; Shutong Wu; Lin Chen; Shichao Meng; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Early warning of urban heavy metal pollution based on PMF- MeteoInfo model combined with physicochemical properties of dust - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Xinying Zhang; Wei Yu; Rong Yu; Xinyu Liu (Stochastic Environmental Research and Risk Assessment, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Three-dimensional DNA biomimetic networks (B-3D Net)-based ratiometric fluorescence platform for cancer-related gene biosensing - Chao Yao; Guiqun Zhang; Hongling Tao; Yulong Li; Rong Hu; Yunhui Yang (Analytica Chimica Acta, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Generation of golden goldfish Carassius auratus via tyrosinase gene targeting by CRISPR/Cas9 - Huijuan Li; Xiaowen Wang; Rong Zhang; Lili Liu; Hua Zhu (Aquaculture, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

Artificial infection pathway of largemouth bass LMBV and identification of resistant and susceptible individuals - Ya Zhang; Bin Gui; Zhihui Jia; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Development and validation of an in situ high-resolution technique for measuring antibiotics in sediments - Yanying Li; Qiuyu Rong; Chao Han; Hanbing Li; Jun Luo; Liying Yan; Degao Wang; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Intraparticle sorption and desorption of antibiotics - Cheng Zhang; Rong Li; Dongfang Ke; Hongri Suo; Shuai Wang; Enze Ma; Yulong Chen; Chongxuan Liu (Journal of Hazardous Materials, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

Biochar improves the humification process during pig manure composting: Insights into roles of the bacterial community and metabolic functions - Yanan Yin; Xiaohui Tao; Yifei Du; Mengtong Li; Sai Yang; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2024)

The effect of lactic acid bacteria fermentation on physicochemical properties of starch from fermented proso millet flour - Tongze Zhang; Siqi Hong; Jia-Rong Zhang; Pin-He Liu; Siyi Li; Zixian Wen; Jianwei Xiao; Guirong Zhang; Olivier Habimana; Nagendra P. Shah; Zhongquan Sui; Harold Corke (Food Chemistry, 2024)

The optimal ammonium-nitrate ratio for various crops : A Meta-analysis - Jiatao Chen; Jinghua Li; Weifang Li; Peng Li; Rong Zhu; Yuxiu Zhong; Weifeng Zhang; Tingyu Li (Field Crops Research, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

A layered sodium-ion host O3-NaFe0.5Ti0.5O2 enables Na-free cathodes through offering extractable Na-ions - Qingyang Song; Peng Shi; Zhiqiang Guo; Peng Zhang; Yuanhang Li; Xiaohui Rong; Xiaoyan Wu; Shuyin Xu; Huican Mao; Yingchun Lyu; Chengjun Zhu (Chemical Engineering Journal, 2024)

3D microprinting of QR-code integrated hydrogel tactile sensor for real-time E-healthcare - Zi-Rong Li; Tian-Run Lv; Zhenxu Yang; Wen-Hai Zhang; Ming-Jie Yin; Ken-Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2024)

Stereoisomerically enhanced polynorbornene-imide dielectric energy storage performance - Hongmei Qin; Man Liu; Shiyu Qin; Shixian Zhang; Xingnan Zhou; Chenjian Li; Yuhao Wei; Dan Chen; Rong Fan; Shan Wang; Quanling Yang; Chuanxi Xiong; et al. (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

A multi-species pest recognition and counting method based on a density map in the greenhouse - Zhiqin Zhang; Jiacheng Rong; Zhongxian Qi; Yan Yang; Xiajun Zheng; Jin Gao; Wei Li; Ting Yuan (Computers and Electronics in Agriculture, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Effects of zinc oxide nanocomposites on microorganism growth and protection of physicochemical quality during maize storage - Dong-Dong Zhang; Jin-Feng Zhao; Li-Qin Tan; Qiong Wu; Hao-Xin Lv; Yu-Rong Zhang; Min Zhang (International Journal of Food Microbiology, 2024)

High-efficient sunlight-driven hydrogen production from methanol steam reforming on a novel photo-thermo-catalysis and thermo-catalysis dual-bed reactor - Donghui Li; Jie Sun; Zhenwen Zhang; Rong Ma; Jinjia Wei (Fuel, 2024)

A study of volatiles of young citrus fruits from four areas based on GC–MS and flash GC e-nose combined with multivariate algorithms - Qian Zhang; Rong Xue; Xi Mei; Lianlin Su; Wei Zhang; Yu Li; Jinguo Xu; Jing Mao; Chunqin Mao; Tulin Lu (Food Research International, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Introducing local-molecule trap in a cost-effective metal–organic framework for C2H2/CO2 separation - Xue-Qian Wu; Tao He; Peng-Dan Zhang; Jiamei Yu; Jian-Rong Li (Chemical Engineering Journal, 2024)

High tensile properties, wide temperature tolerance, and DLP-printable eutectogels for microarrays wearable strain sensors - Xiaomin Zhang; Youjie Rong; Huijie Li; Jianhua Fei; Xiaobo Huang; Qingbo Bao; Jian An (Chemical Engineering Journal, 2024)

Engineered oxidation states in NiCo2O4@CeO2 nanourchin architectures with abundant oxygen vacancies for enhanced oxygen evolution reaction performance - Shiyu Xu; Peng Zhang; Rong Zhao; Jong Wook Bae; Hao Li; Jin Yong Lee; Pil J. Yoo (Chemical Engineering Journal, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Systematic investigation of peracetic acid activation by UV/ferric(III) hydrate oxide for efficient degradation of norfloxacin: Mechanisms and applications - Xinrui Guo; Rong Li; Yongjun Zhang; Shunlong Pan (Chemical Engineering Journal, 2024)

Reactant enrichment in yolk-shell structured Pd/TiN nanoreactors for boosting electrocatalytic hydrodechlorination performance - Jun Zhang; Chunyuan Wang; Shiyu Lu; Shuyue Liu; Pingjuan Liang; Huan Yi; Mengjie Li; Meng Jin; Rong Wang; Guangming Jiang (Chemical Engineering Journal, 2024)

Relationships between different types of biochar and N2O emissions during composting based on roles of nosZ-carrying denitrifying bacterial communities enriched on compost and biochar particles - Yanan Yin; Mengjin Gu; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Bioresource Technology, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Ferroptosis: underlying mechanisms and involvement in neurodegenerative diseases - Yi Wang; HongJing Li; QianXiong He; Rong Zou; JinRui Cai; Lin Zhang (Apoptosis, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Applicability evaluation of innovative simplified methods of slatted floor in pig houses – A CFD study - Fei Qi; Xuedong Zhao; Zhengxiang Shi; Li Rong; Guoqiang Zhang; Hao Li (Computers and Electronics in Agriculture, 2024)

Application and evaluation of probiotics against red rot disease in Pyropia - Peiwen Weng; Huichao Yang; Zhaolan Mo; Wenbin Zhang; Yongwei Yan; Xiaojun Rong; Jie Li (Aquaculture, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Influence of drought intensity on soil carbon priming and its temperature sensitivity after rewetting - Rui Zhang; Rong Li; Jialiang Kuang; Zhenqing Shi (Science of The Total Environment, 2024)

Enhancing the removal of chlorinated hydrocarbons from groundwater using a new BL5 microorganism with functional CS@ZVI materials - Zhiguo Chen; Wenqing Cao; Yan Li; Jingpeng Song; Yiyun Liu; Juncheng Liu; Rong Zhang; Rongxin Su; He Bai (Journal of Water Process Engineering, 2024)

Exploring carbon content variation in microplastics sequestrated from seawater to sediment in the Haima cold seep area - Xiao-Nan Wu; Jing-Chun Feng; Xiao Chen; Can-Rong Li; Si Zhang (Journal of Hazardous Materials, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Preparation of size-tunable Fe3O4 magnetic nanoporous carbon composites by MOF pyrolysis regulation for magnetic resonance sensing of aflatoxin B1 with excellent anti-matrix effect - Zhou Xu; Yanqiu Chen; Rong Wang; Maolong Chen; Jian Zhang; Yunhui Cheng; Bangben Yao; Li Yao; Jianguo Xu; Wei Chen (Food Chemistry, 2024)

TBK1 upregulates the interferon response against virus by the TBK1-IRF3/7 axis in yellow catfish (Pelteobagrus fulvidraco) - Li-ming Xiong; Lei Zhang; Zhe Long; Xiang Zhao; Yan-rong Ying; Tiao-yi Xiao; Shu-ting Xiong (Fish & Shellfish Immunology, 2024)

Insights into current bio-processes and future perspectives of carbon-neutral treatment of industrial organic wastewater: A critical review - Xinzheng Zhang; Yuqin Fan; Tianwei Hao; Rong Chen; Tao Zhang; Yong Hu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

Mechanistic insights into synergistic facilitation of copper/zinc ions and dewatered swine manure-derived biochar on anaerobic digestion of swine wastewater - Gaojun Wang; Changxi Sun; Peng Fu; Bo Zhang; Jinglin Zhu; Qian Li; Jianfeng Zhang; Rong Chen (Environmental Research, 2024)

Iron isotope evidence in continental intraplate basalts for mantle lithosphere imprint on heterogenous asthenospheric melts - Rong Xu; Sarah Lambart; Oliver Nebel; Ming Li; Zhongjie Bai; Junbo Zhang; Ganglan Zhang; Jianfeng Gao; Hong Zhong; Yongsheng Liu (Earth and Planetary Science Letters, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Genome dosage alteration caused by chromosome pyramiding and shuffling effects on karyotypic heterogeneity, reproductive diversity, and phenotypic variation in Zea–Tripsacum allopolyploids - Yingzheng Li; Xu Yan; Mingjun Cheng; Zizhou Wu; Qiyuan Zhang; Saifei Duan; Yong Zhou; Huaxiong Li; Shipeng Yang; Yulin Cheng; Wansong Li; Lulu Xu; et al. (Theoretical and Applied Genetics, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)